A rapid 3D reproduction system of dam-break floods constrained by post-disaster information. (May 2021) - Li, Weilian; Zhu, Jun; Fu, Lin; Zhu, Qing; Guo, Yukun; Gong, Yuhang
Abstract: The 3D reproduction of dam-break floods plays a key role in emergency management and disaster information dissemination. However, existing systems for the simulation of floods have some deficiencies. First, the input data parameters are complex. Second, the simulation process is cumbersome and time consuming, and it lacks a complete workflow. In this paper, we develop a platform for the rapid 3D reproduction of dam-break floods. Key technologies, such as numerical models of dam-break floods based on cellular automata (CA), 3D reproduction constrained by post-disaster information, and dynamic augmented representation, are discussed in detail. Then, two typical dam-break flood cases are selected for experimental analysis. The experimental results show that the system can support the rapid 3D reproduction of dam-break floods constrained by post-disaster information. Compared with that of other simulation systems, the reproduction time is reduced to less than 1 h, and this system supports rapid reproduction at different times and positions. Highlights: Compared with other simulation systems, the rapid dam-break flood reproduction system has the following advantages: First, the reproduction time of the flood process is reduced to less than 1 h. The simulation of the spatiotemporal process of a dam-break flood is a very complex process, and abundant input data and parameters are needed to achieve accurate simulation. The current flood system focuses on the mechanism and simulation accuracy and avoids a large time investment in data processing and simulation, which is inconsistent with the goal of rapid response to flood disasters. The rapid flood reproduction system simplifies the input parameters of the model and reduces the model calculation time. Furthermore, the system integrates input data processing, spatiotemporal simulation and augmented representation into a complete workflow, reducing the entire reproduction time to one hour level and providing decision-making support for disaster response. Second, this system supports rapid 3D reproduction of flood processes at different times and positions. A flexible parameter configuration is provided. The cross-section data, flow data, and dry and wet depth are required to set in the current flood simulation software. The system proposed in this paper has a simplified parameter configuration; users only need to set several necessary parameters, such as the DEM, roughness and storage capacity. Furthermore, on this system, users can quickly visualize dam-break flood disasters at different times and locations. In addition, different from the current flood systems offered to professionals, the rapid dam-break flood system provides a user-friendly interface, hides potential technical details such as model calculations, and reduces user requirements with respect to professional background and experience. Third, augmented representation improves the transmission efficiency of flood disaster information. In the flood disaster management, users pay more attention to flood disaster information than to visual effects. Augmented representation allows visualization of the cause, process and result of dam-break floods through the combination of static representation and dynamic representation and a logical sequence, which can enhance the transmission of flood disaster information and the user's perception level.